Charge Neutralization Strategy: A Novel Synthetic Approach to Fully Cationized Thiolate‐Protected Au25(SR+)18 Clusters with Atomic Precision. Issue 5 (2nd March 2017) - Ishida, Yohei; Huang, Yu‐Ling; Yonezawa, Tetsu; Narita, Kunihiro
Abstract: Many thiolate‐protected molecular Au clusters, of different cluster sizes and with varying neutral or anionic thiolate ligands, have been reported over the past two decades. Despite this abundance of information, to date there has been no report of atomically pure cationized molecular Au clusters that are protected with cationic thiolates. We herein present a novel, facile and high‐yield synthetic approach towards producing a new series of thiolate‐protected molecular Au clusters: a fully cationized Au25 (SR + )18 cluster with atomic precision. The simple "charge neutralization strategy" presented enables treatment of the cationic thiols as neutral thiols, thus the well‐established method for preparing Au25 clusters with neutral thiolates can be adopted for cationic Au25 clusters at a very high synthetic yield. We believe that this report will widen the spectrum of gold cluster chemistry and also help in the further development of cationized molecular clusters with various metals, core sizes, and ligand structures. Abstract : Many thiolate‐protected molecular Au clusters, of different cluster sizes and with varying neutral or anionic thiolate ligands, have been reported over the past two decades. In this paper, a novel, facile and high‐yield synthetic approach to produce a new series of thiolate‐protected molecular Au clusters is presented.